Pandemics, Protests, and Publics - Sarah Shugars; Adina Gitomer; Stefan McCabe; Ryan J. Gallagher; Kenneth Joseph; Nir Grinberg; Larissa Doroshenko; Brooke Foucault Welles; David Lazer (Journal of Quantitative Description: Digital Media)
As an integral component of public discourse, Twitter is among the main data sources for scholarship in this area. However, there is much that scholars do not know about the basic mechanisms of public discourse on Twitter, including the prevalence of various modes of communication, the types of posts users make, the engagement those posts receive, or how these things vary with user demographics and across different topical events. This paper broadens our understanding of these aspects of public discourse. We focus on the first nine months of 2020, studying that period as a whole and giving particular attention to two monumentally important topics of that time: the Black Lives Matter movement and the COVID-19 pandemic. Leveraging a panel of 1.6 million Twitter accounts matched to U.S. voting records, we examine the demographics, activity, and engagement of 800,000 American adults who collectively posted nearly 300 million tweets during this time span. We find notable variation in user activity and engagement, in terms of modality (e.g., retweets vs. replies), demographic subgroup, and topical context. We further find that while Twitter can best be understood as a collection of interconnected publics, neither topical nor demographic variation perfectly encapsulates the "Twitter public." Rather, Twitter publics are fluid, contextual communities which form around salient topics and are informed by demographic identities. Together, this paper presents a disaggregated, multifaceted description of the demographics, activity, and engagement of American Twitter users in 2020.